Impact of covid-19 on the Islamic law of burial: An evaluation in perspective of Shariah objectives and Islamic legal Maxims - Nabeela Falak (jihat-ul-islam, 2020)
This research paper aims to study and evaluate Islamic law of burial in context of death by epidemic (covid-19). Pandemic covid-19 brings impact to all aspects of human life, including in Islamic Fiqh. Therefore, Islamic fiqh continues to develop along with the development of the dynamics of community life and the problems of the age that surrounds it. As the number of coronavirus (COVID-19) deaths continues to rise across all regions of the world. Every culture and community has its own set of rituals to help ease the pain. Under Islamic law, as in many cultures and religions, the management of dead bodies is the object of specific rules that aim at ensuring the dignity and respect of the dead as well as for their living relatives. The nature and sheer scale of the current coronavirus (COVID-19) pandemic, however, has created a number of questions, challenges and even rumors in Muslim majority states as well as for Muslim communities around the world. In handling the remains of COVID-19 victims, whether in Muslim or non-Muslim majority states, Islamic rules developed by Muslim jurists and Islamic authorities must be guided by two considerations: First, the lives of body handlers and rest of the community must not be endangered. The protection of life (Hifẓ al-nafs) is the first of the five ultimate objectives of Islamic law (maqāṣid al-sharīʻah)Second, according to Islamic burial rituals, the dignity of the dead and the emotions of their loved ones are to be respected as much as is practically possible in extraordinary situations such as armed conflicts, epidemics, disasters or other catastrophes. This pragmatic approach is characteristic of Islamic law, as evidenced in the Islamic legal maxims pertinent to the COVID-19 pandemic: For example “al-ḍarar yuzāl”( Harm must be removed), and “Al-Mashaqqah tajlib al-taysīr”( Hardship begets ease) etc.This paper finds the impact of pandemic(covid-19) on law of burial in perspective of objectives of Islamic sharīʻah and Islamic Legal maxim.